Music to counter violence: a preventative approach for working with adolescents in schools. - Nöcker-Ribaupierre M; Wölfl A (Nordic Journal of Music Therapy, 2010)
In countries with an increasing migrant population, more and more children are forced to deal with different cultures and limited language skills. Increasing violence and difficulty with social integration are often the results. The following music therapy approach, based on research and clinical experience, is designed to alleviate such problems. The basic clinical aim is to support children and young adolescents in order for them to express their emotional state and aggressive tension. Regulation of affect and aggression, resolution of conflict situations, avoidance and resistance of threatening situations, and constructive handling of aggression can be practiced musically, within a thematic framework. Working creatively on specific subjects promotes reciprocal respect, acceptance of individual differences and social integration. Particularly in classes with migrant children from diverse cultures, experiencing common rhythmic improvisation can lead to a breaking down of barriers. Despite language and social differences, an emotionally stabilizing feeling of togetherness can develop, experienced in a playful manner and therapeutically supported. This approach, created and developed from clinical music therapy practice against the background of the current school situation in Germany, is piloted in two Munich boarding schools.